Public Transport Accessibility for People With Disabilities - Endang Sri Wahyuni; Bhisma Murti; Hermanu Joebagio (Journal of Health Policy and Management, 2016)
Background: Data from the Ministry of Social Services Republic of Indonesia Social Ministry in 2009 showed there were 1,541,942 people with disability in the Indonesian population. Problems often arise regarding access to public-transportation services for people with disability. Despite the existence of UU No 4 in 1997 and UU No 25 in 2009 on accessibility for people with disability, public transport seemed to be poor for them. This study aimed to determine the public transport accessibility for people with disabilities and to provide alternative solutions.Subjects and Methods: This was a qualitative explorative study. Data were obtained from people with physical and mental disability, and provider (Division Head, Surakarta Public Transport Service Bureau). Data were analyzed using triangulation.Results: The local government of Surakarta has provided some transport facilities. However, these transport facilities are in low standard and non-accessible to people with disability. Transportation accessible to people with disability is not of priority. According to the provider this was because of limited budget. Consultation and coordination amongst the providers were on going in order to provide better transportation system accessible to people with disability.Conclusion: Transportation system was not accessible to people with disability. But the government provider in charge of transportation is planning to provide transportation system to people with disability.  Keywords: transportation, facility, accessibility, disability, public services transportation.Correspondence: Endang Sri Wahyuni. Department of Occupational Therapy, Health Polytechnic Surakarta.Journal of Health Policy and Management(2016), 1(1): 1-7https://doi.org/10.26911/thejhpm.2016.01.01.01